Paediatric dental treatment under inhalation sedation by a therapist in secondary care: An audit. (2nd December 2020) - Palmer, Elara; Campbell, Sarah-Jayne; Foo, Lee
Abstract : We investigated the success of paediatric dental treatment under inhalation sedation (IHS) with nitrous oxide completed by a dental therapist, as an alternative to general anaesthesia (GA) in secondary care. We found that 94% of had treatment successfully completed under IHS by a therapist. These patients were assessed as being suitable for IHS and were referred to the therapist via a new patient clinic. The success of therapists treating paediatric patients with IHS could help reduce pressure on GA waiting lists. As well as being a safer treatment option, this method allows effective conservative treatment to be completed and thereby reducing the number of extractions required, which is a major benefit to patients' future health and wellbeing. CPD/Clinical Relevance: This study shows the success of treatment under inhalation sedation by a dental therapist. Appropriate referral to therapists has the potential to reduce the need for procedures under general anaesthesia. This has the affect of reducing the strain on our general anaesthetic waiting lists, as well as having a positive impact on the health and wellbeing of our patients with IHS being considered the safer option.